PROMOSI TRADISI JONG TITIS OBJEK WISATA PANTAI BETING BERAS KUALA MERBAU KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Wulandari, Ulfa Fitri; Sidiq, Rd. Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted in Kuala Merbau Village, Meranti Islands Regency, precisely on the Jong Titis tourism tradition, in this case it was motivated by problems arising in a less effective promotion system. The promotion carried out could make the Indonesian people know more widely about Malay traditions in the Regency. Meranti Islands. This research aims to find out how promotions are carried out by managers and the obstacles faced in introducing and highlighting tourism potentials in Merbau Island District and preserving traditional folk games on Merbau Island. This research uses a qualitative method with a descriptive approach. Researchers used interview, observation and documentation techniques and the results of this research show that the implementation of the promotion of the Jong Titis tradition still needs to be improved. Apart from that, the management must increase the participation of Pokdarwis members and local residents. Keywords: Promotion, Tradition, Jong Titis.